Inflammatory Myofibroblastic Tumor of the Trachea with Concomitant Granulomatous Lymph Node Lesions - Julia Anne Koch; Patrick Dorn; Thierry Rausch; Hans-Beat Ris; Hans-Anton Lehr; Stephan C. Schäfer (Case Reports in Medicine)
We report herein the case of a 57-year-old lady who had two concomittant lesions, an inflammatory myofibroblastic tumor in the trachea, and severe granulomatous lesions in the adjacent hilar lymph nodes. While these two lesions shared histological and some immunohistochemical features lesions. They differed in terms of ALK-1 expression, which was positive in the tracheal tumor and negative in the lymph nodes. The discussion of the case circles around putative pathophysiological links between the lesions. The authors favor the idea that the lymph nodes present a sarcoid-like granulomatous reaction to the inflammatory myofibroblastic tumor in the trachea over a coexistence of two independent entities. However, no conclusive evidence for this interpretation can be presented based on the existing literature.